Experiential knowledge: Dance as source for popular music historiography. Issue 3 (30th September 2020) - Peter, Beate
Abstract : This article is concerned with the retrieval of sources in popular music historiography. It discusses the methodological and conceptual challenges that popular music historians might encounter when faced with cultures or practices that cannot be fully captured through conventional paradigmatic principles of the treatment of sources. Discussing an over-reliance on written documentation and a focus on what is identified as theoretical knowledge, a case is made for the inclusion of experiential knowledge as source for popular music history. Understood to be contextualized knowledge that can only be gained through participation in a music event, the article identifies dance as a form of experiential knowledge, which can be used to describe and explain music events such as raves. Understanding dance as/in memory provides opportunities to establish stronger links between the sociology of everyday life and the historical treatment of events.